Plasma pTau 181 concentrations in middle‐aged, community‐dwelling, racially and ethnically diverse adults. (20th December 2022) - Brickman, Adam M.; Lao, Patrick J.; Banjoko, Michael B.; Mayeux, Richard; Simoes, Sabrina; Manly, Jennifer J
Abstract: Background: Plasma biomarkers for Alzheimer's disease (AD) are becoming more widely available, with pTau181 emerging as among the most sensitive and specific. There is a lack of data characterizing plasma pTau181 concentration in diverse cohorts and in middle age. The purpose of this study was to examine the association of age, sex/gender, race/ethnicity, APOE genotype, and memory with plasma pTau181 in the Offspring Study of Racial and Ethnic Disparities in Alzheimer's Disease study, a population‐representative study of AD risk in middle aged adults. Method: We included 1041 participants (56±11‐years‐old [range: 28‐88], 68% women, 13±3 years education, 49% Latinx tested in Spanish, 24% Latinx tested in English, 20% non‐Latinx Black, 7% non‐Latinx White, 28% with APOE‐ε4 ). Blood samples were analyzed for pTau181 concentration (Quanterix Simoa) and APOE genotype, and memory was evaluated with the Selective Reminding Test (SRT). We used general linear models to examine associations of pTau181 concentration with the variables of interest. We also examined differences in memory among subgroups of participants defined with a model‐based clustering approach based on the distribution of Ptau181 concentrations. Result: PTau181 concentrations were 1.87±1.21 pg/mL (range: 0.071‐16.15). Increased age (β=0.016 [0.009‐0.023], p<0.001) and male sex/gender (β=‐0.274 [‐0.436‐ ‐0.111], p<0.001) were associated with higher pTau181, but APOE‐ε4 genotype (β=‐0.008 [‐0.176‐0.161], p=0.930) was not. PTau181 did not differ between Latinx participants tested in Spanish (reference group) and Latinx participants tested in English (β=0.151 [‐0.048‐0.350], p=0.136), non‐Latinx Black (β=0.150 [‐0.056‐0.357], p=0.153), or non‐Latinx White (β=‐0.031 [‐0.284‐0.345], p=0.849) participants. Higher pTau181 was associated with lower SRT delayed memory scores in an unadjusted model (β=‐0.442 [‐0.661‐ 0.22], p<0.001) and after adjustment for age, sex/gender, race/ethnicity, education, and APOE status (β=‐0.366 [‐0.577– ‐0.154], p<0.001). We identified three clusters of participants, corresponding to relatively low, medium, and high pTau181 concentrations. The highest cluster had poorer memory performance than the other groups in fully adjusted models (F=5.56, p=0.004). Conclusion: Plasma pTau181 concentrations are associated with memory, sex/gender, and age in midlife. We do not find evidence of race/ethnicity or APOE related differences in pTau181 concentrations in this age group.